The crawl stroke kick - not propulsive but it aids progression (1999)
The common attributions of kicking in crawl stroke technique are erroneous. Kicking facilitates speed swimming by facilitating streamline, supporting more powerful and effective arm strokes, and counter-balancing vertical force components involved in arm actions. Kicking does not contribute to propulsion in a direct way.